Influence of different nozzle hole orifice diameter on performance, combustion and emissions in a diesel engine. Issue 2 (3rd May 2020) - Vijay Kumar, M.; Veeresh babu, A.; Ravi Kumar, P.; Manoj Kumar Dundi, T.
Abstract: In this article, the experimental tests were carried out to explore the performance, combustion and emissions by modifying the different nozzles hole size injectors such as (3 holes × Ø = 0.20 mm (modified)), (3 holes × Ø = 0.28 mm (Base)) and (3 holes × Ø = 0.20 mm (modified)). The experiments are performed on Kirloskar 4-stroke computerised solitary cylinder diesel engine fuelled with diesel at 1500 rpm, water-cooled direct injection diesel engine with eddy current dynamometer with the standard injection timing of 23° bTDC with an injection pressure of 210 bar was maintained constant throughout the experiment. From the results, it was pointed out that in all the three different nozzles (3 holes × Ø = 0.20 mm (modified)) improves the vaporisation, atomisation and air-fuel mixing are resulting in a shorter duration. The impressive results are seen in the performance, combustion and emissions. The only negative aspect is the NOx increasing with small orifice Nozzle Hole Diameter.